2007
DOI: 10.1074/jbc.m700906200
|View full text |Cite
|
Sign up to set email alerts
|

RAS/ERK Signaling Promotes Site-specific Ribosomal Protein S6 Phosphorylation via RSK and Stimulates Cap-dependent Translation

Abstract: Converging signals from the mammalian target of rapamycin (mTOR) and phosphoinositide 3-kinase (PI3K) pathways are well established to modulate translation initiation. Less is known regarding the molecular basis of protein synthesis regulated by other inputs, such as agonists of the Ras/extracellular signal-regulated kinase (ERK) signaling cascade. Ribosomal protein (rp) S6 is a component of the 40S ribosomal subunit that becomes phosphorylated at several serine residues upon mitogen stimulation, but the exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
630
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(671 citation statements)
references
References 41 publications
(53 reference statements)
33
630
8
Order By: Relevance
“…We suspect this is because RSK remains activated. In support of this idea, RSK has been reported to phosphorylate S6RP on its S235/236 residue (Roux et al, 2007). We showed that P-RSK levels decreased with the loss of p110a following YB-1 or PIK3CA knockdown (Figures 5b and c), demonstrating that the phosphorylation of this protein is also PI3K dependent.…”
Section: Mda-mb-231supporting
confidence: 64%
See 1 more Smart Citation
“…We suspect this is because RSK remains activated. In support of this idea, RSK has been reported to phosphorylate S6RP on its S235/236 residue (Roux et al, 2007). We showed that P-RSK levels decreased with the loss of p110a following YB-1 or PIK3CA knockdown (Figures 5b and c), demonstrating that the phosphorylation of this protein is also PI3K dependent.…”
Section: Mda-mb-231supporting
confidence: 64%
“…Therefore, we queried if loss of p110a affected P-S6RP levels in an AKTindependent manner. Alternatively, RSK is also known to phosphorylate S6RP on its Ser235/236 residue (Roux et al, 2007). Indeed, similar to P-S6RP, P-RSK (S380) levels decreased after reduction in p110a subsequent to silencing YB-1 or PIK3CA.…”
Section: Mda-mb-231mentioning
confidence: 99%
“…The ERK1/2 signaling pathway has the ability to regulate proteins involved in the initiation and elongation stages of mRNA translation in an mTOR-dependent and -independent manner (28,35,43,44). Recent studies indicated that ERK signaling is involved in later phase anabolic responses after resistance exercise (5,6,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, the translation of 5'TOP mRNAs is unaffected in hepatocytes from both S6K1 -/-/2 -/-knock-out mice 9 and rpS6 P-/-mice 10 . A recent study provided evidence that site specific phosphorylation of rpS6 on Ser(235/236) via Rsk promotes cap-dependent translation by facilitating the formation of pre-initiation translation complexes 11 .…”
Section: Introductionmentioning
confidence: 99%